Aspectos técnicos e econômicos da pecuária de corte em sistemas lavoura-pecuária-floresta - Silva, Nágela Maria Faustino da (2017)
The use of integrated systems is one of the best options to guarantee improvements in livestock production with sustainability. The objective with this study was evaluate beef cattle productivity in forage-based production systems. The experiment was carried out at Embrapa Agrossilvipastoril, Sinop/MT from August/2015 to July/2016. The experiment followed a randomized complete block design, with 5 systems and four replications, totaling 20 experimental units (paddock), with two hectares each. Five production systems were evaluated: livestock (L); livestock-forestry (iLF); croplivestock (iCL); crop-livestock-forestry (iCLF); and crop-livestock-forestry-harvesting (iCLFE). In rainy season, the highest values of forage accumulation (AF) (11,220 kg ha-1 ), percentage of leaf (% F) (92.1%), weight gain per area (GPA), mean daily gain (GMD) (1.090 g day-1 ) and minimum stocking rate (TLmin) (1.12 UA ha-1 ), mean (TLméd) (4.07 UA ha-1 ) and maximum TLmax) (7.72 AU ha-1 ). These results, coming from better climatic conditions, such as higher rainfall index, contributing to the development of forages and, consequently, of animals. The systems with higher yields of both forage (MF, AFT, DF and OF) and of the animal (TLmin, TLméd, TLmax, GMD and GPA) were those preceded by tillage (iCL and iCLF). The highest GPA in iCLF is due the residual effect of crop fertilization, which resulted in increased forage production in iCL (20,540 kg ha-1 ) and iCLF (20,700 kg ha-1 ) systems. The gain weight per area in iCLF system (30.9 @ ha-1 ) was 27.3% higher than iCL and 66% higher than L and iLF treatments. The synergy between the crop, livestock and forest components promotes greater meat production in iCLF system. Systems of croplivestock, livestock-forestry and crop-livestock-forestry are sustainable intensification alternatives to produce beef cattle in the Brazilian Amazon. The second objective was to analyze the costs of crop-livestock-forest production scenarios. Six scenarios were delineated and analyzed over a period of eight years: 1 - modal cattle raising (Pm); 2 - intensified animal husbandry (Pi); 3 - crop-livestock integration (iLP); 4 - forest animal husbandry (iPF); 5 - crop-livestock-forest integration (iLPF) and 6 - modal crop (L). The highest total cost was in the iLPF system, in which it presented R $ 9,572.68 / ha, secondly the iLP with R $ 9,512.87 / ha, later the Pi with R $ 4,943.52 / ha, the iPF with R $ 4,465.13 / ha, the Lm with R $ 4,220.45 and finally the Pm with R $ 1,565.00 / ha. The producer has the option of the production system that best suits his technical skills and financial condition for investment.